Corporate Governance - The Role of Various Stakeholders - Anuradha Reddy, M.; Akula, Ravi (Prabandhan: Indian Journal of Management, 2011)
Corporate governance is the set of processes, customs, policies, laws, and institutions affecting the way a corporation is directed, administered or controlled. Corporate governance also includes the relationships among the many stakeholders involved and the goals for which the corporation is governed. The principal stakeholders are the shareholders, management, and the board of directors. Other stakeholders include labour (employees), customers, creditors (e.g., banks, bond holders), suppliers, regulators, and the community at large. Corporate governance is a multi-faceted subject. An important theme of corporate governance is to ensure the accountability of certain individuals in an organization through mechanisms that try to reduce or eliminate the principal-agent problem. A related but separate thread of discussions focuses on the impact of a corporate governance system in economic efficiency, with a strong emphasis on shareholders' welfare. This paper is a modest attempt to discuss the practices of corporate governance as well as the role of various stakeholders.